Penerapan Metode Full Time Equivalent Untuk Mengukur Beban Kerja Pada Unit Tml-1 (Receiving Area) PT. GMF Aeroasia Tbk - Akbar Rizky Saputra; Ismail Fardiansyah; Tri Widodo (Journal Industrial Manufacturing, 2026)
Human resource management (HRM) is one of the success factors of a company, because by implementing human resource management in a company it will provide an even distribution of workload and the number of workers in a company. Unit TML-1 is one of the units in PT. GMF Aeroasia which is tasked as a Receiving Area service, where in 2024 the unit has a high number of overtime. This study aims to calculate the workload, analyze and determine improvements in the workload conditions of the TML-1 unit using the Full Time Equivalent (FTE) method. Based on the analysis that has been carried out on 3 positions in the TML-1 unit, the senior officer position has a normal category, Officer 1 and 2 have a normal category, while the PKWT position has an overload category with an FTE value of 8.57. After getting the FTE value, the proposal given to the TML-1 unit is to increase the number of workers in the PKWT position by 5 people so that the workload category becomes normal. Keyword: workload analysis, full time equivalent, rating factor, lead time, human resource management.